Impact of COVID-19 on the sport activity of families and children doing sport - Stoilov, I.; Naydenov, A. (Knowledge - International Journal, 2021)
The impact of Covid-19 and damages on social-economic life will last for many year ahead. Extremely affected by the pandemic proved to be the area of sport - for the first time in the 124-years history of modern Olympic Games same have been disallowed, , without the world being in war. The measurement of losses is not limited to financial side only. The aim of the present article is to establish the impact of pandemic and dissemination of Covid-19, on the health status of separate individuals, possibilities for practicing sport with children and the effect from the strict quarantine measures, on the sport community and the society as a whole. Participants in the investigation have been parents of children doing sport, inquiring 656 adult persons in the period 15-30 April, 2020. Parents have filled in an inquiry card containing 25 main and 7 demographic questions. For processing of the results we have used SPSS, version 26. We have measured quantitative and qualitative indications. The exceptional situation has influenced rather negatively the separate individuals and their families, and the most serious influence in a negative aspect being on their physical condition. 56% of the individuals under inquiry had no possibilities for regular sport trainings, and almost 88% of them attach it to the imposed prohibitions during the quarantine. Over 70% of parents deem that on-line education could not be applicable in future, at raising the prohibitions, but 30% of them are of the opinion that video materials and on-line education could be used in future. The extraordinary situation has influenced rather negatively on the separate individuals and their families, and the most serious influence in a negative aspect being on their physical condition. In their bigger part the individuals under inquiry deem that the situation with Covid-19, will reflect negatively on the sport clubs and their activity in future.